Nutraceuticals and Fortified Foods Supplements in India: Challenges and Opportunities - A Comprehensive Review - Tahilani, Praveen; Banweer, Jitendra; Chatterjee, D P; Goyanar, Gaurav; Sharma, Abhishek (Indian Journal of Pharmacy & Drug Studies, 2023)
Background: As the growing interest in the overall health of the community the term nutraceuticals, functional food ingredients, and dietary supplements are gaining importance worldwide. Objective: The study aimed to identify and study the importance of food fortification and the importance of nutraceuticals for their efficacy and effectiveness in India. Methods: Pubmed and Google Scholar were searched and only article and information relevant to the topic was selected for review. Results: A total of 53 articles were selected for review which included information about the nutraceuticals and fortified Foods Supplements. Conclusion: There are no scientifically proven functional foods for improving public health. There is a requirement to change the platform of a balanced and nutritious diet required for healthy people.